The Giant Pairing Vibration in Carbon isotopes. (July 2016) - Cavallaro, M.; Cappuzzello, F.; Carbone, D.; Agodi, C.; Azaiez, F.; Assié, M.; de Séréville, N.; Scarpaci, J. A.
Abstract: The 13 C( 18 O, 16 O) 15 C and 12 C( 18 O, 16 O) 14 C reactions at 84 MeV incident energy were explored up to high excitation energy of the residual nucleus thanks to the use of the MAGNEX spectrometer to detect the ejectiles. In the region above the two-neutron separation energy, a resonance has been observed in both nuclei, attributed to the Giant Pairing Vibration (GPV). The neutron decay of the 15 C resonances, including the GPV, populated via the two- neutron transfer reaction has been studied using an innovative technique, which couples MAGNEX with the EDEN neutron detector array. The data show that the 15 C GPV mainly decays via two-neutron emission.